Dua Dekade Pembangkangan Sipil (Civil Disobedience) Masyarakat Agam: Menguak Akar Hukum, Religius, Kultural dalam Menolak Peraturan Pemerintah - Muhammad Taufik; Alfan Miko; Indraddin; Bob Alfiandi; Abdul Halim (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This research analyses the sociological and normative lawfulness of the civil disobedience initiated by the Agam community against the implementation of Government Regulation (PP) No. 84 of 1999, examined through the dual lenses of Maqasid al-Shari’ah and sociolegal theory. Employing a sociolegal research framework, the study integrates a normative-doctrinal analysis of Islamic legal literature with empirical field investigations to deconstruct the occurring legal tensions in West Sumatra. The findings demonstrate that the resistance against the proliferation of Nagari territories does not constitute an act of rebellion (bughat); rather, it represents a form of mu’aradhah shar’iyyah (legitimate constitutional opposition) and an implementation of the principle of amr ma’ruf nahi munkar. State policies that potentially disenfranchise communal land sovereignty (ulayat) are found to contravene the Shari’ah principles of preserving communal property (hifz al-mal) and lineage (hifz al-nasl), thereby failing to satisfy the legal maxim that government policies must be predicated upon the welfare of the people (tasharruf al-imam manuthun bi al-maslahah). From the perspective of Shari’ah jurisprudence, this civil disobedience is justified as a mechanism for preventing harm (dar’u al-mafasid) caused by repressive centralized regulations. This study underscores the imperative of harmonizing the laws of the state, customs (adat), and Shari’ah to avert structural injustice within the framework of regional autonomy.